Ecohealth:: research experiences and innovative practices to understand linkages between health, ecosystems and society - Távora, Renata (Sustainability in Debate, 2018)
Dominique F. Charron (editor). Ecohealth Research in Practice ”“ Innovative Applications of an Ecosystem Approach to Health. Ottawa, ON, Canadá, International Development Research Centre (IDRC) & Springer, 2012. 282 páginas. ISBN: 978-1-4614-0516-0. 179,00 (Hardcover). Fotografias, figuras, gráficos, índice remissivo, lista de colaboradores, mapas, referências bibliográficas, tabelas.